(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article reflects on the political-legal, socio-economic, and spiritual-educational views of the enlightenment poet Siddiqiy Ajziy, as well as the tragic fate of a nation, caught in the vortex of ignorance, left behind in the development of Turkestan. The discussion revolves around the idea that the purpose of literature and poetry is to heal the wounds of the homeland and nation, and to call them towards knowledge, enlightenment, and progress.